RETURN ON EQUITY HAS AN EFFECT ON DEBT TO EQUITY RATIO AND WORKING CAPITAL TURNOVER OF PROPERTY AND REAL ESTATE SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) PERIOD 2018-2022 - Maulana, Yono Maulana; Sari, Maya; Puteri, Mega Yusdian (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to determine